Kings in all but name the lost history of Ouchi rule in Japan, 1350-1569 - Conlan, Thomas D. 1968- (Oxford scholarship online, 2024)
In the 16th century, members of the Ōuchi family were kings in all but name in much of Japan. Immensely wealthy, they controlled sea lanes stretching to Korea & China, as well as the Japanese city of Yamaguchi, which functioned as an important regional port with a growing population & a host of temples & shrines. The family was unique in claiming ethnic descent from Korean kings, & such claims were recognized in both Korea & Japan. Their position, coupled with dominance over strategic ports & mines, allowed them to facilitate trade throughout East & Southeast Asia. They also played a key cultural role in disseminating Confucian texts, Buddhist sutras, ink paintings, & pottery, & in creating a distinctive, hybrid culture that fused Japanese, Korean, & Chinese beliefs, objects, & customs. This book shows how Japan was an ethnically diverse state from the 14th through the 16th centuries